OBCs and the ruling classes in India - Verma, H. S. (ed.) (Jaipur, 2005)
Despite the fact that the OBCs constitute the largest chunk of the Indian society, they are the single most neglected social-constitutional category. This is the first book that attempts to empirically answer crucial questions about their present status and treatment of the OBC problematic by different Fractions of the ruling coalition. It is divided into four parts. The first part deals with their composition and characteristics. The second part analyses the role of the politico-administrative Fractions deciding the key questions of methodology of identification and scheduling of the ABCs, the anomalies in the listing, the creamy layer, the Composition and decomposition, characteristics, and institutional mechanisms handling different empowerment tasks. The third part highlights the role of the opinion- makers. The fourth part presents the acts of Commissions and omissions by the bar and the judiciary. The book is likely to trigger a whole new sets of studies on the ABCs and the caste-based inequalities in India. It would be an essential reading for social scientists, policy planners, political parties and the ABCs themselves.
Keywords: Other backward Classes